ISLAMIC VALUE-BASED COMMUNITY ENVIRONMENTAL LITERACY AND EDUCATION AS A FRAMEWORK FOR CIRCULAR ECONOMY AND SUSTAINABLE WASTE MANAGEMENT - Nurhayati, Sri; Angga Setra; Taufikin, Taufikin (Humanities Journal of University of Zakho, 2025)
Rural waste management presents multifaceted challenges, particularly where cultural and religious values strongly shape environmental practices. This study examines the integration of Islamic ethical principles within a community-driven waste management framework to strengthen environmental stewardship, foster sustained community engagement, and generate socio-economic benefits. Using a qualitative case study methodology, research was conducted at an Integrated Waste Management and Recycling Center (IWMRC) in a rural Indonesian village. Before the establishment of the IWMRC, local waste practices relied heavily on unregulated dumping and open burning, resulting in substantial environmental and public health risks. Since the center’s operation in 2019–2024, the IWMRC has managed approximately 60 tons of waste annually, produced 20 tons of compost, and generated Rp 9,600,000 (USD 600) per year in revenue through waste bank activities, with active participation from about 280 local households and vendors (representing approximately 56% of the community). Thematic analysis reveals that Islamic values such as Khilafah (stewardship), Taharah (cleanliness), Amanah (trustworthiness), and Shura (consultative governance) are systematically embedded in technical operations and community education, guiding waste segregation, composting, and public learning. Circular economy principles, realized through waste bank programs, offer economic incentives that empower residents and improve livelihoods. Governance structures founded on justice (Adl), public welfare (Maslahah), and inclusive consultation support institutional resilience and sustainability. While early results are promising, this study acknowledges the limited follow-up period and recommends continued monitoring to assess long-term outcomes. These findings offer valuable insights for culturally attuned and sustainable waste management in Muslim-majority rural contexts.